Susceptibility to and severity of SARS-CoV-2 infection according to prescription drug use–an observational study of 46,506 Danish healthcare workers - Eiken, Aleksander; Bliddal, Sofie; Villumsen, Marie; Iversen, Kasper K.; Bundgaard, Henning; Hasselbach, Rasmus B.; Kristensen, Jonas H.; Nielsen, Pernille B.; Pries-Heje, Mia M.; Knudsen, Andreas D.; Fogh, Kamille; Norsk, Jakob B.; et al. (PloS one, 2024)
It is not well investigated whether exposure to specific drug classes is associated with COVID-19. We investigated the risk of SARS-CoV-2 infection and severe COVID-19 among healthcare workers according to prescription drug use. We conducted an observational study among Danish healthcare workers. SARS-CoV-2 positivity was defined as a positive PCR/ELISA test throughout 2020 and severe COVID-19 as any above 48-hour hospitalization within 14 days after infection. Patient characteristics came from online surveys while data on SARS-CoV-2, drugs and hospitalizations came from Danish Health Registers. Infected individuals were matched with uninfected controls based on age, sex, and chronic diseases. Drug exposure was defined as any prescription redemption in the past six and one month(s) before infection for each drug class. Models assessing the risk of infection (conditional logistic regression) and severe COVID-19 (logistic regressions) versus drug usage were adjusted for BMI, smoking, alcohol, education, region, and patient contact when possible. We matched 5,710 SARS-CoV-2-infected cases with 57,021 controls. The odds of infection were reduced by calcium channel blocker (adjusted odds ratio (aOR) 0.81, 95% Confidence Interval (CI): 0.66–1.00) and vasoprotective drug (aOR 0.77, CI: 0.62–0.95) usage during the six months before infection compared to no usage. Exposure to antibacterials in the past month increased the odds of infection (aOR 1.27, CI: 1.09–1.48). Among infected participants, the odds of severe COVID-19 were higher with usage of almost any investigated drug, especially, diuretics (crude odds radio (OR) 4.82, CI:2.15–10.83), obstructive airway disease drugs (OR 4.49, CI: 2.49–8.08), and antibacterials (OR 2.74 CI:1.62–4.61). In conclusion, antibacterials were associated with more SARS-CoV-2 infections and calcium channel blockers with less. Once infected, users of prescription drugs had higher odds of developing severe COVID-19. These findings suggest a need for studies to clarify interactions between specific drug groups, behaviour, known risk factors, and disease susceptibility/severity.